Impact of COVID-19 on percutaneous coronary intervention for ST-elevation myocardial infarction - Kwok, Chun Shing; Gale, Chris P; Kinnaird, Tim; Curzen, Nick; Ludman, Peter; Kontopantelis, Evan; Wu, Jianhua; Denwood, Tom; Fazal, Nadeem; Deanfield, John; de Belder, Mark A; Mamas, Mamas (Heart (British Cardiac Society), 2020)
BackgroundThe objective of the study was to identify any changes in primary percutaneous coronary intervention (PCI) for ST-elevation myocardial infarction (STEMI) in England by analysing procedural numbers, clinical characteristics and patient outcomes during the COVID-19 pandemic.MethodsWe conducted a retrospective cohort study of patients who underwent PCI in England between January 2017 and April 2020 in the British Cardiovascular Intervention Society-National Institute of Cardiovascular Outcomes Research database. Analysis was restricted to 44 hospitals that reported contemporaneous activity on PCI. Only patients with primary PCI for STEMI were included in the analysis.ResultsA total of 34 127 patients with STEMI (primary PCI 33 938, facilitated PCI 108, rescue PCI 81) were included in the study. There was a decline in the number of procedures by 43% (n=497) in April 2020 compared with the average monthly procedures between 2017 and 2019 (n=865). For all patients, the median time from symptom to hospital showed increased after the lockdown (150 (99–270) vs 135 (89–250) min, p=0.004) and a longer door-to-balloon time after the lockdown (48 (21–112) vs 37 (16–94) min, p<0.001). The in-hospital mortality rate was 4.8% before the lockdown and 3.5% after the lockdown (p=0.12). Following adjustment for baseline characteristics, no differences were observed for in-hospital death (OR 0.87, 95% CI 0.45 to 1.68, p=0.67) and major adverse cardiovascular events (OR 0.71, 95% CI 0.39 to 1.32, p=0.28).ConclusionsFollowing the lockdown in England, we observed a decline in primary PCI procedures for STEMI and increases in overall symptom-to-hospital and door-to-balloon time for patients with STEMI. Restructuring health services during COVID-19 has not adversely influenced in-hospital outcomes.